ACADEMIC PHYSICAL EDUCATION AND SPORTS SYSTEM: GENDER ASPECT - Mikhailova, E.Y.; Utisheva, E.V.; Zakrevskaya, N.G.; Androsova, G.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to survey and analyze the gender split situation in the national academic physical education and sports system. Methods and structure of the study. We sampled the students (n=2524 including 1298 men and 1226 women) of Lesgaft National State University of Physical Education, Sport and Health for the gender split analysis. Results and conclusion. We believe that the modern sports communities are virtually free of any gender biases that are still alive in the non-sporting population groups as myths and gender stereotypes – albeit they also tend to fade with time. A good case in point is provided by the latest progress of the men’s rhythmic and artistic gymnastics and synchronized swimming disciplines. It should be mentioned in this context that some gender inequality is still traditional for the national educational system management groups including the academic physical education and sports management which is still dominated by men like quite a few other sectors.